Improving the efficiency of healthcare supply chain in Thailand. (2nd August 2019) - Kritchanchai, Duangpun; Muangchoo, Sophon; Tan, W.K. Albert
Electronic data interchange (EDI) has been very successfully implemented in the manufacturing sector but not in healthcare supply chain (HSC). In the case of the healthcare sector, the adoption of EDI to facilitate interoperability between HSC partners, in particular the pharmaceutical companies and hospitals, is rather slow. One of the reasons is the use of data standard in this EDI system. In this research, several conditions ranging from manual method to the use of an automated EDI system with standard data in a centralised datapool, to accomplish information exchange between a hospital and its suppliers were evaluated. The results indicated that the use of such an EDI system with the centralised datapool would reinforce collaboration between HSC partners and improve its supply chain efficiency.